Development of a Biomarker Panel to Predict Cardiac Resynchronization Therapy Response: Results from the SMART-AV Trial - Spinale, Francis G. (Heart Rhythm, 2018)
BACKGROUND: Predicting a favorable cardiac resynchronization therapy (CRT) response holds great clinical importance. OBJECTIVE: To examine proteins from broad biological pathways and develop a prediction tool for response to CRT. METHODS: Plasma was collected from patients prior to CRT (SMART-AV trial) whereby a CRT response was pre-specified as a ≥15 mL reduction in LV end-systolic volume (LVESV) at 6 months, which resulted in a binary CRT response (Responders: 52%, Non-Responders: 48%; n=758). RESULTS: Candidate proteins (n=74) were evaluated from the inflammatory, signaling, and structural domains, which yielded 12 candidate biomarkers, but only a subset of these demonstrated predictive value for CRT response: soluble suppressor of tumorgenicity-2, soluble tumor necrosis factor receptor-II (sTNFr-II), matrix metalloproteinases-2, and C-reactive protein. These biomarkers were used in a composite categorical scoring algorithm (Biomarker CRT Score), which identified patients with a high/low probability of a response to CRT (p<0.001) when adjusted for a number of clinical covariates. For example, a Biomarker CRT Score of 0 yielded 5 times higher odds of a response to CRT compared to a Biomarker CRT Score of 4 (p<0.001). The Biomarker CRT Score demonstrated additive predictive value when considered against a composite of clinical variables. CONCLUSION: These unique findings demonstrate that developing a biomarker panel for predicting individual response to CRT is feasible and holds potential for point of care testing and integration into evaluation algorithms for patients presenting for CRT.